Assessing childhood maltreatment exposure using the child behavior checklist - Makino, Takuya; Nishitani, Shota; Takiguchi, Shinichiro; Yao, Akiko; Fujisawa, Takashi X.; Tomoda, Akemi (Frontiers in Child and Adolescent Psychiatry, 2025)
IntroductionChildhood maltreatment (CM) has broad and severe adverse effects in later life, but there are not enough studies conducted during childhood close to the time of maltreatment. Most studies have focused only on a single symptom and have not attempted to capture the global picture of CM.MethodsWe used the Child Behavior Checklist (CBCL) to assess children's behavioral/emotional problems more comprehensively. This study leveraged 32 CM children and 29 typically developing (TD) children who have been assessed using the CBCL 4–18 from our dataset. Group comparisons of the eight subscales were conducted to characterize each behavioral/emotional problem. Receiver Operating Characteristic (ROC) curve analysis was conducted to assess the classification performance. Finally, sensitive period and type analyses were performed based on the children's maltreatment history.ResultsThe CM group showed significantly higher behavioral/emotional problems in seven out of the eight subscales. Logistic regression analysis was performed using all combinations of CBCL subscale T-scores and age, sex, and IQ. We created 2047 models and performed ROC analysis for each. Three models were generated: the most accurate model (comprising CBCL T-score, age, sex, and IQ; sensitivity: 0.906, specificity: 0.966), a model excluding IQ (sensitivity: 0.875, specificity: 0.931), and a model consisting only of CBCL (sensitivity: 0.906, specificity: 0.862). The CBCL demonstrated robust predictive capacity for CM by utilizing information provided by caregivers, without directly inquiring about trauma. The sensitive period analysis revealed that the temporal predictor of severity for “withdrawn” and “thought problems” were exposure to CM at age five. Similarly, exposure to CM between the ages of five and seven predicted “somatic complaints”. In the case of type, physical abuse was the predictor for “somatic complaints” and “delinquent behavior”, and emotional abuse was the predictor for “anxious/depressed” and “thought problems”.ConclusionMaltreated children present a wider range of behavioral/emotional problems, which must be considered when supporting them. Perspectives gained from sensitive analyses of maltreatment history will help clinicians provide more appropriate interventions.